Unpacking the parallel effects of parental alcohol misuse and low income on risk of supervisory neglect. (July 2017) - Lloyd, Margaret H.; Kepple, Nancy Jo
Abstract: Although low income status and parent alcohol misuse are considered critical risk factors for child neglect, little is known about the mechanisms of this association. No known research has assessed the parallel effect of each on occurrence of child neglect. This study aimed to explore the direct and indirect effects of parent alcohol misuse and low family income on risk of supervisory neglect through mediating factors such as parent depressive symptoms and low social support. The study used a sample of 2990 parents of children under 13 years old who completed a listed telephone survey conducted in 50 mid-sized cities within California during 2009. We used a structural equation model to estimate the direct and indirect effects of parent alcohol misuse (defined as heavy drinking frequency) and low family income on supervisory neglect toward a focal child, as well as the indirect effect via parental depressive symptoms and low social support. Mediation analysis to capture direct, indirect, and total effects of these two independent variables was also conducted. Results revealed a significant direct effect of low family income on likelihood of supervisory neglect. Low income also exhibited an indirect effect via increased depressive symptoms and low social support. Annual frequency of heavy drinking showed no direct effect on supervisory neglect likelihood, but an indirect effect was observed via increased depressive symptoms and decreased social support. Parent low income and high frequency heavy drinking likely increase risks for supervisory neglect through distinct pathways. Longitudinal research is needed to confirm the pathways identified within this study.